Literature Review Faktor Penyebab Keterlambatan Penyediaan Rekam Medis Rawat Jalan - Arief Tarmansyah Iman; Nursanie Puspita (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
The provision of outpatient Medical Records (MR) affects the length of waiting time for patient services. The time of providing outpatient MR in several hospitals was more than the standard average time of ≤10 minutes. This study aims to analyse the factors causing the delay in providing outpatient medical records. Method: The research design was systematic review uses Google Scholar and Garuda Databases with topics related to factors causing delays in the provision of outpatient MR. Two reviewers were screening and found articles which match the criteria and have 13 full-length articles included to final review. The average time for providing outpatient MR was in range of 11-20 minutes. The causes of delays in providing outpatient MR were grouped based on 5M factors including lack of MR educated officers, indiscipline, lack of knowledge, train and motivation (Man), unavailability of funds (Money), unavailability of MR, storage and folder, easily damaged material, infrastructure unavailability and technical problems (Machine), as well as unavailability and not maximized SOP use, no evaluation and outpatient registration flow (Method). The time delay in providing outpatient MR was still high, the main cause was the unavailability of infrastructure and the lack of MR educated officers.